Patients' Experiences of Engagement with Healthcare Services Following a High-Risk Self-Harm Presentation to a Hospital Emergency Department: A Mixed Methods Study. Issue 1 (2nd January 2022) - Cully, Grace; Leahy, Dorothy; Shiely, Frances; Arensman, Ella
Abstract: Experiences of engaging with healthcare services following a self-harm presentation to hospital of high lethality or high suicidal intent have not been examined previously, despite this subgroup of self-harm patients being at high risk of suicide. Therefore, this study addressed this issue by documenting patients' experiences of engaging with healthcare services after a high-risk self-harm (HRSH) presentation to hospital. Demographic, psychiatric and psychosocial factors associated with variations in perceptions of care received were also examined. Quantitative information was obtained by interview administered questionnaires 0–3 months following a HRSH presentation to hospital. Semi-structured follow-up interviews, conducted, 6–9 months later, provided qualitative data ( n = 32). Satisfaction with aftercare varied. Positive experiences of care included " supportive and compassionate relationships " and " timely and comprehensive follow-up care. " The establishment of trust in the services encouraged help-seeking and psychotropic treatment adherence. Conversely, " superficial and unsupportive relationships " and " care lacking continuity and comprehensiveness " left some participants feeling isolated, contributing to inhibited help-seeking and resistance to psychotropic treatment. Participants with a history of self-harm and mental health service engagement were more likely to report dissatisfaction with care provided. Those who described unsupportive relationships more frequently reported repeated self-harm, alcohol misuse, and hopelessness at follow-up. Our findings show that satisfaction with services, help-seeking and treatment adherence may be improved by ensuring the consistent provision of timely, comprehensive and supportive aftercare following a HRSH presentation. Absence of these aspects of care may contribute to ongoing distress and further suicidal behavior.